(Drying Analysis of Sliced Spring Onions) - Alamsyah, Rizal; Mahdar, Putiati; Mustika, Yang Dewi (Balai Besar Industri Agro, 1994)
The study was desiged to investigate drying characteristics of sliced spring onions (Allium porrum L.) using experimental dryer. The drying experiments were employed with fresh and blanched spring onions based on thin layer drying. The drying experiments were conducted using different drying temperature (46C,52C,and 62C),drying air velocity (3,5 m/s and 4,5 m/s)as well as the size of materrials (0.25 cm x 0.25 cm and 0.5 x 0.5 cm). The drying characteristics obtained were presented as curves i.e. the descrease of moisture content versus time, and drying rate versus moisture content.The drying rates of fresh spring onions were generally higher than those of blanched spring onions.